Llewellyn Castle : a worker's cooperative on the Great Plains - Entz, Gary R. (University of Nebraska Press, 2013)
In 1869, six London families arrived in Nemaha County, Kansas, as the first colonists of the Workingmen's Cooperative Colony, later fancifully renamed Llewellyn Castle by a local writer. These early colonists were all members of Britain's National Reform League, founded by noted Chartist leader James Bronterre O'Brien. As working-class radicals they were determined to find an alternative to the grinding poverty that exploitative liberal capitalism had inflicted on England's laboring poor. Located on 680 acres in northeastern Kansas, this collectivist colony jointly owned all the land and natural resources, with individuals leasing small sections to work. The money from these leases was intended for public works, health, and education of the colony members. The colony floundered after just a few years and collapsed in 1874, but its mission and founding ideas lived on in Kansas. Many former colonists became prominent political activists in the 1890s, and the colony's ideals of national fiscal policy reform and state ownership of land were carried over into the Kansas Populist movement. Based on archival research throughout the United States and the United Kingdom, this history of an English collectivist colony in America's Great Plains highlights the connections between British and American reform movements and their contexts.--description provided by publisher.